2010
DOI: 10.1167/iovs.09-4426
|View full text |Cite
|
Sign up to set email alerts
|

Glucose-6-phosphate-dehydrogenase Deficiency as a Risk Factor for Pterygium

Abstract: The results of this study, although restricted to a limited group of subjects (i.e., those of Sardinian ancestry), suggest that G6PD- not only does not protect against pterygium, but may even be considered a risk factor for the development of this disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…Our diabetic patients with G6PD deficiency showed that the endothelial cells of retinal vessels respond to angiogenic cues and form new vessels. A recent report on pterygium (a benign growth of conjunctival fibroblasts) documents that nucleated cells of G6PD-deficient individuals, when in need of NADPH and pentoses for the synthetic activities of rapid growth, can compensate for the instability of G6PD by increasing its production [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our diabetic patients with G6PD deficiency showed that the endothelial cells of retinal vessels respond to angiogenic cues and form new vessels. A recent report on pterygium (a benign growth of conjunctival fibroblasts) documents that nucleated cells of G6PD-deficient individuals, when in need of NADPH and pentoses for the synthetic activities of rapid growth, can compensate for the instability of G6PD by increasing its production [7].…”
Section: Discussionmentioning
confidence: 99%
“…Sardinia has one of the highest incidences of type 1 diabetes in the world [6], second only to Finland, and a very high prevalence of G6PD deficiency (present in 12-15% of the male population compared with 0.48% in continental Italy) [2]. In Sardinia, all variants of G6PD deficiency are due to the same mutation, which results in only 5-10% residual activity of the enzyme [7] and G6PD deficiency does not show an association with diabetes [8]. We could thus plan to compare the prevalence and severity of retinopathy in diabetic patients with a homogeneously severe degree of G6PD deficiency and in patients with the same duration of type 1 diabetes and the same glycaemic control but with normal G6PD activity.…”
Section: Introductionmentioning
confidence: 99%
“…In another study of 54 children with sickle retinopathy, researchers found that G6PD deficiency is more common in patients with proliferative retinopathy though not statistically significant [15]. Moreover, analysis of 123 pterygium patients with Sardinian ancestry suggests that G6PD deficiency is a risk factor for the development of pterygium [16]. These studies show that subjects with G6PD deficiency are under risk for certain ocular diseases.…”
Section: Increased Risk For Cataract Retinopathy and Pterygium In G6mentioning
confidence: 95%
“…13 The genetic defect also affects nucleated cells, but the pathogenic implications are less well understood. 14 Peiretti and colleagues found an association between G6PD deficiency and a heightened risk of pterygium development, presumably due to a decreased ability of the affected conjunctival fibroblasts to protect themselves from the UV-induced oxidative injury. 14 Such an association suggests that G6PD deficiency confers greater sensitivity to oxidative stress in nucleated cells as well.…”
mentioning
confidence: 99%
“…14 Such an association suggests that G6PD deficiency confers greater sensitivity to oxidative stress in nucleated cells as well. 14 G6PD plays an important role in the antioxidant defense of the cornea. 15 During CXL, the cornea is first soaked with riboflavin and then exposed to UVA light.…”
mentioning
confidence: 99%